Impact of international trade on the quality of the natural environment: A case study of Ghana from 1970 to 2010 - Anaman, K.A.; Twerefou, D.K.; Appiah-Konadu, P. (ResearchGate, 2015)
While trade openness has existed in Ghana since independence in 1957, economic liberalization policies implemented in Ghana starting from April 1983 to present date have led to a significant increase in trade openness. However, the impact of increased trade liberalization on the natural environment still remains unclear. In this work, we estimate the scale, technique and composition effects of trade liberalization on Ghana's environment using carbon dioxide emissions as proxy for environmental degradation and data for the period 1970 to 2010. The results indicate that in the long-run period, international trade has had adverse effects through the increased emissions of carbon dioxide as a result of increasing urbanization. However, increasing per capita income over the period has also reduced emissions of carbon dioxide illustrating the technique effect that increasing wealth of the individual leads to improved demand for higher quality of the environment. Similar results were obtained for the short-run period with the negative scale effect of increasing carbon dioxide emissions from increasing urbanization, and the positive technique effect arising from reduction of emissions from increasing per capita income being observed.
Keywords: Environmental; macroeconomics; Natural resource economics; Macroeconomics and the environment; Pollution; Trade liberalisation